Estimation of the Thermo-Physical Properties of Foods using Substances Contents in the Temperature Range of -40°C to +40°C - Kumar , Sanoj (Journal of Postharvest Technology, 2016)
An easy way to calculate thermal conductivity, specific heat, density and  thermal diffusivity for foods using the percentage contents by classes of  substances (water, proteins, fats, carbohydrates, fibers and ash) using the MS Excel program has been presented and a comparison has been made with the  available method. The comparison shows that quadratic expressions of Choi  and Okos (1986) method may be replaced with the developed models, which  are using straight line equations. This work utilized the MS-Excel worksheet to  develop models for the thermal properties of five food components (viz: fat;  protein; carbohydrate; fiber; and ash), water and ice using Choi and Okos  model to generate data. The results of correlation coefficients of the generated  data using the developed models, show that: the values of R2 for: thermal  conductivity ranges between 0.997 and 1; thermal diffusivity ranges between  0.991 and 1; specific heat ranges between 0.995 and 0.999; while that of  density is 1. The R2value in the case of water and ice properties i.e., thermal  conductivity, thermal diffusivity, specific heat and density are in the range of  0.918-1 and 0.981-1. This shows that the developed models may be used in the  temperature ranges from -40°C to 40°C.
Keywords: conductivity,; comparison; quadratic; properties; coefficients